Le programme de recherche du CIPEA sur les petits ruminants - International Livestock Centre for Africa (1980)
Description of the ILCA Research Programme on small ruminants, with reference to the humid zone of West Africa, particularly Nigeria; data on sheep and goat flocks, livestock ownership and its distribution by size of holding, farming systems in ILCA research areas in Nigeria; mortality rates in animals, and fecundity rates of ewes and does derived from herd composition. Outline of the improvement of existing systems.